The Transcriptome Profiling of Flavonoids and Bibenzyls Reveals Medicinal Importance of Rare Orchid Arundina graminifolia - Ahmad, Sagheer; Gao, Jie; Wei, Yonglu; Lu, Chuqiao; Zhu, Genfa; Yang, Fengxi (Frontiers in Plant Science, 2022)
Orchids are very special flowering plants that take a long time to finish their juvenile phases before flowering. Their slow growth is the major hurdle to studies involving medicinal constituents. Arundina graminifolia is a rare orchid that grows fast unlike other orchids and this characteristic makes it an ideal plant to study the medicinal efficacy of orchids. However, nothing is documented on the genetic pathways of important flavonoids and bibenzyls in this valuable species. Therefore, this study claims the identification of important medicinal components in various parts of A. graminifolia. Transcriptome analysis was performed for five stages (FD1-FD5) of flower development and four tissue types (mature flower, silique, root and leaf) to ascertain genetic regulators of flavonoids and bibenzyls. Weighted Gene Coexpression Network Analysis (WGCNA) was performed to identify the coexpression modules and the candidate genes involving biosynthesis pathways of these chemicals. HPLC-MS/MS was used to quantify bibenzyls and flavonoids in various plant parts. The selected candidates were validated through qRT-PCR. The results approve the presence of bibenzyls and flavonoids in different parts of plant. Therefore, this study sets a fine ground to dissect the presence of important medicinal components in orchids through their gene regulatory pathways.